Patterns of treatment for peripheral arterial disease in the United States: 1996-2005 - Rowe, Vincent L.; Lee, William; Weaver, Fred A.; Etzioni, David (Journal of vascular surgery, 2009)
Endovascular procedures are increasingly used in the treatment of peripheral arterial disease (PAD). Whether this new procedural approach translates to clinical outcomes equivalent or superior to open surgical revascularization is a subject of debate. We sought to analyze population-based rates of major amputations for PAD during a time period in which the use of endovascular surgical procedures increased dramatically. We used the 1996-2005 Nationwide Inpatient Sample (NIS) to analyze rates of amputations and vascular interventions, and also to characterize the treatment of patients admitted acutely for PAD. Vascular interventions were designated based on International Classification of Diseases (ICD) procedure codes as open bypass, endovascular intervention, or major amputation (disarticulation at ankle or higher amputation). Population-based age-adjusted incidence rates of treatment were calculated by combining procedure rates with census data. Our analysis included 97,000 acute admissions for PAD, 83,000 major amputations, 77,500 endovascular procedures, and 171,000 open vascular bypass operations. Between 1996 and 2005, population-based rates of acute admissions for PAD decreased by 4.3% per year, open procedures by 6.6% per year, and major amputations by 6.4% per year, whereas endovascular procedures increased by 4.8% per year. Of patients acutely admitted for PAD, the likelihood of undergoing an amputation decreased (30.2% to 21.8%), the likelihood of undergoing an open vascular procedure decreased (34.5% to 26.3%), and the likelihood of undergoing an endovascular operation increased (12.7% to 28.3%). All of these changes were statistically significant at P < .05. The last decade has seen a significant increase in the use of endovascular procedures and a decrease in rates of major amputation. These trends are seen both for patients admitted with acute PAD, as well as in the population in general. While our study was not designed to demonstrate a causal relationship, our findings suggest an association between increased application of endovascular technology and reduced rates of amputation in patients with PAD.